The graphic organizer’s effect on the students’ writing achievement in argumentative paragraph - Hafidz, Moh (D3 English Program Universitas Merdeka Malang, 2021)
The Graphic organizer strategy is visually mapped to organize the general into a particular idea in an argumentative paragraph to develop students’ writing scores. The purpose of this research is to enrich theoretical and practical strategiesin writing paragraph argumentatively. This research is a quasi-experimental study with a Pretest-post-test non-equivalent group and non-random sampling technique to determine the experimental group consisting of 23 participants and the control group consisting of 23 participants. The expert who validated the test was senior English lecturers. And the researcher used Cronbach’s Alpha to measure the reliability, and the result was 0.721 (acceptable). As the result, graphic organizer strategy significantly affected the students’ writing achievement in argumentative paragraphs, especially on the organization aspect. Additionally, this strategy also allowed them to explore their ideas independently and unconsciously builds some connecting words up.DOI 10.26905/enjourme.v6i1.5701